Factors Associated with Failure of Nonoperative Management for Complicated Appendicitis. Issue 8 (August 2019) - Walker, Charles; Moosavi, Ali; Young, Katelyn; Fluck, Marcus; Torres, Denise; Widom, Kenneth; Wild, Jeffrey
In recent years, nonoperative management of complicated appendicitis has become more common. Patients managed nonoperatively do well, but there is a paucity of literature on patients who fail nonoperative management. The purpose of this study was to examine the overall failure rate, morbidity associated with failure, and potential predictors of failure in nonop management of appendicitis. This is a descriptive retrospective review of patients from a single hospital system who were diagnosed with advanced appendicitis and underwent nonop management between January 1, 2007, and November of 2017. The data were obtained through review of patient charts from the electronic medical record. Failure was defined as requirement of an operation due to ongoing infection secondary to appendicitis. There were 183 patients initially managed non-operatively, with 70 patients failing nonoperative management. Patients failing nonoperative management experienced longer hospitalization (6.2 vs 2.9 days, P < 0.0001), and more patients in the failure group required admission to the ICU (10.0% vs 1.8%, P = 0.028). Multivariate analysis revealed that longer duration of symptoms reduced the likelihood of failure (odds ratio: 0.77 [0.64–0.92]). In this retrospective review, 38 per cent of patients failed nonop management of appendicitis. Symptom duration could provide insight for clinicians in assessing the role of non-operative management because increasing symptom duration reduced the likelihood of failure.